2019
DOI: 10.1177/0972063419884412
|View full text |Cite
|
Sign up to set email alerts
|

Competencies Gap in Hospital Management in Tehran, Iran: A Cross-sectional Survey

Abstract: Competent managers are essential to the efficient, effective and responsive of hospitals. This study aims to determine the competencies gaps in hospital management. This cross-sectional survey was carried out using a self-administered questionnaire among 127 hospital managers in the Iran. The questionnaire included 61 items and 11 dimensions. Participants were completed on a five-point scale ranging the level of importance that each proposed competency had in their job and to indicate their proficiency in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…[1][2][3] In addition, inequities in health, lack of access to quality health care and a poorly skilled health workforce represent some of the major challenges facing many countries in the Eastern Mediterranean Region. 4,5 As a result, reforms have been implemented to improve the effectiveness and efficiency of service delivery at the organizational level including streamlining the management structure, focusing more on performance improvement and benchmarking service outcomes. 6,7 The changing healthcare landscape and requirements of service delivery require a new skillset for health professionals; therefore, a novel managerial approach is needed to lead and manage such transition and consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In addition, inequities in health, lack of access to quality health care and a poorly skilled health workforce represent some of the major challenges facing many countries in the Eastern Mediterranean Region. 4,5 As a result, reforms have been implemented to improve the effectiveness and efficiency of service delivery at the organizational level including streamlining the management structure, focusing more on performance improvement and benchmarking service outcomes. 6,7 The changing healthcare landscape and requirements of service delivery require a new skillset for health professionals; therefore, a novel managerial approach is needed to lead and manage such transition and consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence has also shown that managerial competencies are useful for monitoring and improving the performance of managers (Levenson et al, 2006) and improving the productivity of organisations (Macpherson and Holt, 2007). However, the application of such framework in Iran has been limited, most likely due to the lack of understanding of competency and task requirements for hospital managers (Kakemam and Dargahi, 2019b;Kalhor et al, 2016b). The effectiveness and benefits of current formal and informal management training in building hospitals managers' management capacity is doubtful (Kalhor et al, 2016b;Lankarani et al, 2013).…”
Section: Ijwhm 142mentioning
confidence: 99%
“…Furthermore, evidence indicates that managers may not have a full understanding of the complexities of the hospital sector and the health system and how different sectors in the same health system interact (Kalhor et al, 2016b;Lankarani et al, 2013) and lack strategic thinking capacity. The selection of hospitals managers in Iran is still primarily based on social connections rather than open and competitive procedures: a matter of "who you know" rather than what you know and what you are good at (Kakemam and Dargahi, 2019b;Kalhor et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The hierarchy in charge of the hospital is established at the top of the organizational chart, in the form of shared power with the board of directors. The manager's role becomes relevant as the healthcare sector focuses on management of the population and relations with stakeholders [7] and can help in the response capacity and sustainability of health services [10].…”
Section: Hospital Characteristics Manager Profile and Competencesmentioning
confidence: 99%
“…A great majority of national health systems present serious financing problems, largely due to the change in the demographic paradigm and the introduction of new technology, which results in steadily increasing expenditure. According to Siskou et al [8], increased private expenditure on health and development of the sector are associated with the increased demand for services and the shortage of resources and public funding, leading the private sector to fill the gap through increased investment [9,10], but various studies…”
Section: Introductionmentioning
confidence: 99%